Occupational Identity and Motivation of Apprentices in a System of Integrated Dual VET - Hauschildt, Ursel [Verfasser]; Heinemann, Lars [Verfasser]; Piening, Dorothea [Verfasser] (My University, 2010)
"This contribution focuses on the results of a large-scale survey of more than 1500 aprrentices in Bremerhaven, Bremen and Hessia using four different scales to measure occupational identity, organisational and vocational commitment as well as work ethics. Among others, it has been found, that there is no correlation between the development of vocational commitment and vocational identity and the apprentices' social or migration background, whreas a high diversity of tasks, i.e. skills to be obtained by apprentices and their embedment in the work progress is a significant requirement for attractive and successful VET. The findings gained from this analysis also explain the necessity to establish a profound need to improve the quality of cooperation between the two learning venues: vocational schools and training companies." (Autorenreferat, BIBB-Doku)
Keywords: L 8 Diagnostik / Eignung; P 2.3 Auszubildende; T 4.2 Psychologie; Kompetenzdiagnostik; Duales System; Auszubildender; Berufliche Identität; Arbeitsmotivation; Korrelation; Soziale Faktoren; Demografische Faktoren